2014
DOI: 10.1074/jbc.m113.532739
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the DNA Damage Proteins MDC1 and ATM in the Regulation of the Spindle Assembly Checkpoint

Abstract: Background:The spindle assembly checkpoint (SAC) and the DNA damage response (DDR) are two distinct pathways designed to ensure genomic stability. Results: ATM phosphorylation of H2AX at kinetochores recruits MDC1. ATM and MDC1 modulate kinetochore localization and proper assembly of key SAC factors. Conclusion: ATM and MDC1 regulate the SAC. Significance: DDR core proteins maintain genomic stability also by regulating mitosis progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 59 publications
4
58
1
1
Order By: Relevance
“…Townsend et al reported that MDC1 directly interacts with APC/C and that MDC1-depleted cells undergo a very long mitosis (16). In contrast, Eliezer et al reported that MDC1 plays a role in the spindle assembly checkpoint (SAC) and that MDC1-depleted cells actually have a shorter mitosis (32). Our results clearly showed that MDC1 is required for normal mitotic progression and that MDC1-deficient cells display prolonged mitosis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Townsend et al reported that MDC1 directly interacts with APC/C and that MDC1-depleted cells undergo a very long mitosis (16). In contrast, Eliezer et al reported that MDC1 plays a role in the spindle assembly checkpoint (SAC) and that MDC1-depleted cells actually have a shorter mitosis (32). Our results clearly showed that MDC1 is required for normal mitotic progression and that MDC1-deficient cells display prolonged mitosis.…”
Section: Discussionsupporting
confidence: 54%
“…In addition to the DNA damage signaling pathway, it was recently proposed that MDC1 is involved in the regulation of mitosis (16,32). However, the exact role of MDC1 and its regulation during normal cell cycle progression remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be too surprising given the reported lack of ATM activation in GV stage oocytes following DNA damage (Marangos & Carroll 2012). This contrasts with somatic cells where ATM has been implicated in SAC activation after nocodazole treatment (Eliezer et al 2014). Another DDR protein, MDC1, has also been suggested to be able to directly interact with the APC, an interaction that is heightened after DNA damage (Coster et al 2007).…”
Section: R20 J K Collins and K T Jonescontrasting
confidence: 42%
“…Thus, there is a critical need to develop more effective treatments for NPC. NFBD1 (nuclear factor with BRCT domain protein 1), also known as MDC1 (mediator of DNA damage checkpoint protein 1), is a recently identified nuclear protein that regulates many aspects of the DNA damage response (DDR) pathway, such as the intra-S phase checkpoint, the G2/M checkpoint, the spindle-assembly checkpoint and the formation of NBS/MRE/Rad50 (MRN complex), 53BP1 and BRCA1 foci [7][8][9][10][11]. Human NFBD1 comprises 2089 amino acid residues and has a predicted molecular weight of *220 kDa.…”
Section: Introductionmentioning
confidence: 99%